The laws and effects of terahertz wave interactions with neurons - Shaoqing, Ma; Zhiwei, Li; Shixiang, Gong; Chengbiao, Lu; Xiaoli, Li; Yingwei, Li (Frontiers in Bioengineering and Biotechnology, 2023)
Terahertz waves lie within the energy range of hydrogen bonding and van der Waals forces. They can couple directly with proteins to excite nonlinear resonance effects in proteins, and thus affect the structure of neurons. However, it remains unclear which terahertz radiation protocols modulate the structure of neurons. Furthermore, guidelines and methods for selecting terahertz radiation parameters are lacking. In this study, the propagation and thermal effects of 0.3-3 THz wave interactions with neurons were modelled, and the field strength and temperature variations were used as evaluation criteria. On this basis, we experimentally investigated the effects of cumulative radiation from terahertz waves on neuron structure. The results show that the frequency and power of terahertz waves are the main factors influencing field strength and temperature in neurons, and that there is a positive correlation between them. Appropriate reductions in radiation power can mitigate the rise in temperature in the neurons, and can also be used in the form of pulsed waves, limiting the duration of a single radiation to the millisecond level. Short bursts of cumulative radiation can also be used. Broadband trace terahertz (0.1-2 THz, maximum radiated power 100 μW) with short duration cumulative radiation (3 min/day, 3 days) does not cause neuronal death. This radiation protocol can also promote the growth of neuronal cytosomes and protrusions. This paper provides guidelines and methods for terahertz radiation parameter selection in the study of terahertz neurobiological effects. Additionally, it verifies that the short-duration cumulative radiation can modulate the structure of neurons.